Children's Integrity Character Education of Early Childhood Based on School Culture Through The Habituation Program - Feny Nida Fitriyani; Meilina Meilina (AT-TURATS, 2021)
The character of the nation's children is increasingly eroded by the spread of various problems related to moral degradation, such as: corruption, nepotism, and dishonesty. PAUD institutions in this case certainly play an important role in building the initial foundation in children in order to minimize moral degradation. Therefore, character education becomes a solution to overcome this problem. One of the programs launched at TK Masyithoh 25 Sokaraja, Banyumas is integrity education based on school culture through the habituation program. Methodologically, type of this research is field research, while the approach used is qualitative approach. The data are obtained from observations, interviews, and documentation. The results of this study found four types of habituation used in integrity character education, namely routine habituation, spontaneous habituation (giving reward, punishments, and advice), habituation by exemplary, and habituation with conditioning. Each habituation includes stimulus, response, and reinforcement. Reinforcement is an important element in integrity character education through habituation in early childhood. The reinforcement that is mostly used by teachers is positive reinforcement in the form of non-material rewards. These four habituation are the basic way to instill the character of integrity (honesty, exemplary, and politeness) in children at TK Masyithoh 25 Sokaraja as a kindergarten piloting project for integrity education. Keywords: Integrity Character Education, Child Moral, Habituation.